2019
DOI: 10.3390/ijms20133210
|View full text |Cite
|
Sign up to set email alerts
|

Recent Topics on The Mechanisms of Immunosuppressive Therapy-Related Neurotoxicities

Abstract: Although transplantation procedures have been developed for patients with end-stage hepatic insufficiency or other diseases, allograft rejection still threatens patient health and lifespan. Over the last few decades, the emergence of immunosuppressive agents such as calcineurin inhibitors (CNIs) and mammalian target of rapamycin (mTOR) inhibitors have strikingly increased graft survival. Unfortunately, immunosuppressive agent-related neurotoxicity commonly occurs in clinical practice, with the majority of neur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 154 publications
(185 reference statements)
0
25
0
1
Order By: Relevance
“…An experimental study showed that prednisolone acetate 40 mg/kg can induce depression-like behaviour in rhesus macaques [81]. Exogenous corticosterone can cause induction of glutamate at synapses, which contributes to mood disorders [82,83]. Cognitive decline is found to be related to current or long-term steroid use (even low dose) in RA patients as a vascular side effect [72] but another study reported no significant relation between MMSE and chronic glucocorticoid use [74].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…An experimental study showed that prednisolone acetate 40 mg/kg can induce depression-like behaviour in rhesus macaques [81]. Exogenous corticosterone can cause induction of glutamate at synapses, which contributes to mood disorders [82,83]. Cognitive decline is found to be related to current or long-term steroid use (even low dose) in RA patients as a vascular side effect [72] but another study reported no significant relation between MMSE and chronic glucocorticoid use [74].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Calcineurin inhibitors (CNIs) are a class of widely used drugs to prevent graft vs. host disease (GVHD) and its sequelae after HSCT. Cyclosporin A (CsA) and tacrolimus (TAC) are mainly Vasculitis or immune-mediated encephalitis caused by cGVHD Unknown included, they exert immunosuppressive actions by binding to immunophilins to inhibit the calcineurin-mediated calciumdependent signaling pathways that mediate the formation of interleukin-2 and T-lymphocyte activation (27). Although many patients benefit from them, neurotoxicities caused by these agents have remained serious, a seizure is one of the severe manifestations which cannot be ignored.…”
Section: Immunosuppressantsmentioning
confidence: 99%
“…Previous reports have indicated that both CsA and TAC enhance the permeability of the blood-brain barrier (BBB) by damaging tight junctions directly, inducing apoptosis of brain capillary endothelial cells (30), and decreasing P-glycoprotein's efflux pump function (27,31). In addition, CsA exposure can increase nitric oxide (NO) production in brain endothelial and astroglial cells, further mediating endothelial injury and impairment of BBB function (32,33).…”
Section: Immunosuppressantsmentioning
confidence: 99%
“…These EV not only cross the bloodbrain barrier, but also negate concerns regarding the possibility of teratoma formation and immune rejection that confound related stem cell-based approaches [15,17,22]. Immune rejection is a particularly signi cant problem in the case of AD, since the long-term use of immunesuppresants can result in toxicity, particularly in the aged, and may also exacerbate AD-related pathologies [35,58].…”
Section: Mitigation Of Alzheimer's Disease Neuropathologies By Human mentioning
confidence: 99%